The Metaldad and Habitus Metalicus in the city of Lima 1994-2014 - Yépez Aguirre, Jimmy (2019)
This study has been oriented, to identify the benefits of the qualitative method of the theory built on the different aspects of feeling and thinking of the Metaleros1 in the city of Lima, in order to analyze their impersonal relations with society. In this sense the following objective was proposed: to understand why the social life individualization, the cultural commodification and the music fetishism is reproduced in the feeling and thinking of Lima’s metaleros. An in-depth interview was conducted with 23 young adults and metaleros between aged 14 to 48 years old as a range or limit, which resulted in a non-probabilistic sample. Two conceptual categories were identified: Rockandad and Metaldad, which serve to give interpretation to the problematic raised. In addition, a conceptual theoretical instrument called pyramidal dialectic was elaborated, to give way to the explanation of the research carried out.